2004
DOI: 10.1007/s00276-004-0265-8
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and biomechanical investigations of the iliotibial tract

Abstract: Divergent descriptions of the anatomic location and biomechanical function of the iliotibial tract (IT) can be found in the literature. This study attempted to obtain exact data regarding the anatomic course and material characteristics including the biomechanical properties of this structure. The following were its aims: (1) anatomical investigations of the IT; (2) mechanical properties of the IT; (3) femoral head centralizing force of the IT and subligamentous forces in the height of the greater trochanter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
90
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 16 publications
2
90
1
2
Order By: Relevance
“…This finding provides further evidence that knee flexion, by itself, does not play a significant role in the aetiology of ITBS as has been historically believed. 1,21,23 However, the increased peak knee internal rotation angle in the ITBS group measured in the current study is likely an important factor in the development of ITBS. A number of authors have suggested that, due to its insertion on the tibia, increased knee rotation increases torsional loads to the tissues of the knee joint such as the iliotibial band.…”
Section: Data Collection and Analysismentioning
confidence: 68%
See 2 more Smart Citations
“…This finding provides further evidence that knee flexion, by itself, does not play a significant role in the aetiology of ITBS as has been historically believed. 1,21,23 However, the increased peak knee internal rotation angle in the ITBS group measured in the current study is likely an important factor in the development of ITBS. A number of authors have suggested that, due to its insertion on the tibia, increased knee rotation increases torsional loads to the tissues of the knee joint such as the iliotibial band.…”
Section: Data Collection and Analysismentioning
confidence: 68%
“…21,26 Anecdotally, this syndrome has been associated with repetitive flexion and extension on a loaded knee, in combination with a tight iliotibial band. 1,16,[21][22][23] Orchard et al 23 suggested that frictional forces between the iliotibial band and the lateral femoral condyle are greatest at 20° to 30° of knee flexion, which occur during the first half of the stance phase of running. However, despite this well-accepted sagittal-plane theory, 1,21,23 no differences have been found in the few biomechanical investi-…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling studies suggest that: (1) ITB tension increases with HADM and hip adduction angle (Tateuchi et al, 2015) and (2) ITB tension and subsequent compressive forces between the ITB and greater trochanter (gluteal tendon insertion) increase with hip adduction angle (Birnbaum et al, 2004). The impact of greater HADM on gluteal tendon loading is likely to be greater during stair ascent than level walking for several reasons.…”
mentioning
confidence: 99%
“…The gluteal tendons are vulnerable to compression against the greater trochanter and iliotibial band (ITB) (Dwek et al, 2005) as the hip moves into adduction and ITB tension increases (Birnbaum and Pandorf, 2011;Birnbaum et al, 2004). Contraction of the muscles that insert into the ITB (i.e.…”
Section: Introductionmentioning
confidence: 99%